Penyelesaian Sengketa Medik Terhadap Adanya Dugaan Kelalaian Medik oleh Dokter Gigi dalam Perspektif Hukum Kesehatan - Puti Sari Mayang; Khairani Khairani; Siska Elvandari (UNES Law Review, 2023)
Health services lead to health development which aims to achieve awareness, will, and the ability to live healthy for every resident in order to achieve optimal public health status as aspired to in Law Number 36 of 2009 concerning Health. In terms of optimal health services, it is certainly expected to create professional health workers in carrying out their profession, especially dentists. However, in carrying out medical practice, it is possible for a dentist to commit medical crimes that have an impact on the patient's health. Where medical negligence that results in disruption of patient health can result in disruption of medical health between doctors and patients. But not infrequently in terms of legal protection and in solving medical problems there are significant obstacles to solving legal problems. So to answer this problem, it is necessary to know the form of patient legal protection for the existence of medical justice by dentists and how to settle medical settlements between patients and their families and doctors based on the provisions in force in health law. The research method used is descriptive normative research. The results of the study revealed First, that legal protection for patients due to dentist negligence has been specifically accommodated in several laws related to health, but this legal protection has not run optimally because there are still massive obstacles originating from the legal substance of the legal structure and legal culture. who have not been able. Second, the causes for the medical settlement are qualified into three things, namely due to the absence of medical negligence, medical failure and medical malpractice, then in terms of the settlement of medical settlements it has not run optimally either through non-litigation or litigation, therefore the need for a Medical Dispute Settlement Court (PSSM) which specifically resolves cases related to health law in Indonesia.